Effect of Cytokinin, Western bud extract and CuSo4 on some Storage Traits of Fig Fruits of black Diyala cultivar. ( Ficus carica L. ) - Hadi Kadhim Hussein Al-Jubouri; Abbas Mohsen Salman Al-Hamidawi (Kufa Journal for Agricultural Sciences)
This study was conducted in quail as a particular work for the of histopathological disorders between Sept6, 2018 Nov23, 2018 (77 days), to determine the effect of adding cinnamon alcohol extract to diets in ovulation and the fertility rate of the ovary and oviduct tissue in the quail, there are (3 treatments), and they were divided into 12 cages, each group consists of 10 males with 5 females. In the first group, quails were fed on a standard diet without any additives, while in the second treatment, 300 mg/kg of alcoholic extract of cinnamon was added to the quails’ diet, and the third treatment include the addition of 400mg.kg-1 of alcoholic cinnamon extract powder, the results of the histological study showed that the quail diet includes alcoholic cinnamon extract of additives (400 mg per kg) a physiological reproductive activity changes, ovulation and fertility rate were increased without any side effects. In conclusion, the results showed an increase in growth rate and cilia number and ciliated epithelial layer cells in their numbers and shapes in the oviduct, despite the rapid growth and rapid ovulation, unless there was no change in the shape of the egg or a change in its components.